THE HEGEMONY OF AND COUNTERHEGOMONY OVER THE DUTCH GOVERNMENT WITH REFERENCE TO THE TEXT OF GEGURITAN* MEWALI KA KARANGASEM WRITTEN BY A.A. ISTRI AGUNG - Suastika, I Made (International Conference on Cultural Studies; Vol 1 (2018): Proceedings International Conference on Cultural Studies, 2018)
The hegemony of the Dutch Government over the legal power took place gradually in Karangasem. The instruction came from the Dutch Government through Ratu Baginda Putri in Holland (the Dutch Queen), the Batavian Governor General and the Controller (the district officer of the colonial era) in Bali. Who was appointed king should have been genealogically appointed. However, the king was exiled to Jembrana through the Cupel harbor. That took place from 1908 to 1913. However, the king then returned to Karangasem (currently referred to as Amlapura). The text of Geguritan Mewali Ka Karangasem narrates what took place from 1908 to 1920. The most important which is narrated is the death of Dewa Agung Ketut Jelantik (1918). What took place could not be separated from the hegemonic measures taken by the Dutch Government using violence and through “conspiracy” with others, causing the king to be exiled to Jembrana through the Cupel harbor. The writer shows her counterhegemony by what is locally referred to as mandulame, namely repeatedly stating that what had taken place could not be separated from pituduh Widhi (God’s desire). The misery, sorrow and mercilessness resulting from what had taken place is considered what is locally referred to as basma. The value which Geguritan Mawali Ka Karangasem contains is that death is better. What it contains is discussed in detail in this article.